Evaluasi Program Rehab Rumah Layak Huni Bagi Masyarakat Pra Sejahtera Di Kabupaten Jombang - Afandi, Muhamad Nur (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2013)
House is one of primary needs for every individual. The presence of house is a formally entry into variety of development policies, it is related without house or permanent residences, an individual existences would be formally hard recognized (for having Identity Card), and it is an agreement in development policies. Therefore, every individual has right to obtain a feasible occupied house. For realizing it into reality, thus District of Jombang's DinasPekerjaanUmum, CiptaKarya, Tata Ruang, Kebersihan, and Pertamanan provides for assistance in form of feasible occupied house rehabilitation program. Every program implementation must be evaluated in order such implementation is not biased from its predetermined purposes. The house rehabilitative program evaluation conducted by writer implement an evaluative motion spatial phases such as : preparation phase, planning phase, plan implementation phase, and post-development activity phase. This research made use a descriptive qualitative research. Meanwhile, its data collection was carried out by observation, in-depth interview, and documentary research. The credibility test was handled by sources and technic triangulation methods. Data processing was worked by reducing data, data presentation, and presented a concluding illustration on research. The research findings consisted of informant's opinion and interpretation as well as conclusions made by writer. From results obtained, evaluation outcomes show that implementation of feasible occupied house rehabilitation program at District of Jombang has not fully effective one. It is, among others, caused by preparation, planning, and activity implementation phases have not fully effective, too.